تأثير التدريب المركب على فاعلية أداء بعض الركلات لدى لاعبي الكوميتية في رياضة الكاراتيه - علي، أسامة عبدالرحمن; معوض، مجدي المتولي محمد; عبدالحميد، هشام حجازي عبدالحميد; صالح، هاني أحمد عبدالدايم أحمد (جامعة المنصورة - كلية التربية الرياضية, 2015)
The research aims to identify the impact the effectiveness of some kicks of the kumite player in karate. The researcher used the experimental approach on a deliberated sample of the kumite player in Al-Gamalia outh Sports Center and Al- Mataria Youth Sports Center which contains (20) player. After applying the program, the dimensional measurements was conducted and processing data statistically, the most important results reached by the researcher that Compound –Training impacts positively on the effectiveness of some kicks of the kumite player in karate.
يهدف البحث إلى التعرف على تأثير التدريب المركب على فاعلية بعض الركلات لدى لاعبي الكوميتيه في رياضة الكاراتيه، وتم استخدام المنهج التجريبي على عينة عمديه من لاعبي الكوميتيه بمركز شباب الجمالية وبمركز شباب المطرية وبلغت عينة البحث الأساسية (20) لاعب، وبعد الانتهاء من تطبيق البرنامج تم إجراء القياسات البعدية ومعالجة البيانات إحصائياً وكانت أهم النتائج التي توصل لها الباحث أن التدريب المركب يؤثر إيجابياً على فاعلية بعض الركلات لدى لاعبي الكوميتيه في رياضة الكاراتيه.
Keywords: رياضة الكارتيه -- التدريب الرياضي -- اللاعبون -- المهارت الحركية